The Persianate World The Frontiers of a Eurasian Lingua Franca - Green, Nile (University of California Press, 2019)
Persian is one of the great lingua francas of world history. Yet despite its recognition as a shared language across the Islamic world and beyond, its scope, impact, and mechanisms remain underexplored. A world historical inquiry into pre-modern cosmopolitanism, The Persianate World traces the reach and limits of Persian as a Eurasian language in a comprehensive survey of its geographical, literary, and social frontiers. From Siberia to Southeast Asia, and between London and Beijing, this book shows how Persian gained, maintained, and finally surrendered its status to imperial and vernacular competitors. Fourteen essays trace Persian's interactions with Bengali, Chinese, Turkic, Punjabi, and other languages to identify the forces that extended "Persographia," the domain of written Persian. Spanning the ages of expansion and contraction, The Persianate World offers a critical survey of both the supports and constraints of one of history's key languages of global exchange. "This groundbreaking collection illuminates the multifaceted and very complex history of the rise and decline of the Persian language as a lingua franca." AHMAD KARIMI-HAKKAK, author of Recasting Persian Poetry "With erudition and refinement, this book accomplishes something remarkable-it provides a timely corrective to an anachronistic understanding of the Persianate sphere as an empire of letters centred on Iran." PAOLO SARTORI, author of Visions of Justice "An exceptionally important contribution to our understanding of what constituted the Persianate world." ANDREW PEACOCK, University of St. Andrews NILE GREEN holds the Ibn Khaldun Endowed Chair in World History at the University of California, Los Angeles. He is the author of Sufism: A Global History and Terrains of Exchange: Religious Economies of Global Islam and editor of Afghanistan's Islam: From Conversion to the Taliban.